Fluor to manage construction projects for Westinghouse Electric. Issue 10 (October 2015) - Unknown
Abstract : Westinghouse Electric Co LLC has named Fluor Corp to manage construction of two Westinghouse AP1000 nuclear power reactor projects in Georgia and South Carolina, USA.